Physical maps of varicella-zoster virus DNA derived with 11 restriction enzymes. - Mishra, L (1984)
Varicella-zoster virus DNA was digested with 11 restriction endonucleases, and the resulting fragments were separated on agarose gels. Terminal fragments were identified by lambda exonuclease digestion. Physical maps were then constructed using a combination of double restriction enzyme digestion and hybridization to cloned BamHI fragments to place the remaining fragments in order.